Determination of Species‐Specific Differences in Intracranial Volume of Tuj Sheep and Hair Goats Using Stereology and Computed Tomography Methods - Ali Koçyiğit; Betül Kanik; İsmail Demircioğlu; Yasin Demiraslan (Veterinary Medicine and Science)
ABSTRACT The intracranial cavity contains vitally important organs. The brain, cerebellum, meninges and the vessels that supply these organs are located in the intracranial cavity. Therefore, it is important to learn about the intracranial cavity and to study it. However, there is limited information about the intracranial cavity in the veterinary field. The aim of this study was to determine the differences between the intracranial cavities of different species of animals by using stereology and tomography methods, volume calculations and morphometric measurements. In addition, the compatibility of the methods used with each other was investigated. In the study, six male adult goats and six male adult sheep were used. In this study, the intracranial cavities of sheep and goats were calculated by using Cavalieri's principle and 3D modelling using tomography sections. Morphometric measurements were taken over the intracranial space, and index calculations were made. In 3D models using computed tomography, the intracranial volume was 153.31 ± 24.06 cm3 in goats and 128.07 ± 7.93 cm3 in sheep. In the calculation using Cavalieri's principle, it was determined to be 152.73 ± 22.73 cm3 in goats and 126.15 ± 8.38 cm3 in sheep. As a result of the study, the MWCC (maximum width of the cranial cavity) parameter was found to be statistically significant between species (p < 0.05). The two methods used in Bland‐Altman analysis were found to be within the limits of agreement, and the methods can be alternative to each other.